One Pot Solvothermal Synthesis of Organic Acid Coated Magnetic Iron Oxide Nanoparticles - Venegas-Yazigi, D; Venegas-Yazigi, D; Casagrande-Denardin, J (SOC CHILENA QUIMICA, 2013)
In this work we present the synthesis and characterization of iron oxide nanoparticles (IONPs), which were structurally and magnetically characterized. The use of iron salts and an organic acid (l-serine or ascorbic acid) as precursors under solvothermal conditions yielded these coated IONPs. The powder X-ray diffraction pattern of FeO-1 and FeO-2 is consistent with hematite (alpha-Fe2O3) and hematite-maghemite ((alpha-Fe2O3/gamma-Fe2O3) respectively. The TEM analysis permits to estimate an average size of 10 nm for the FeO-1 sample. The magnetic characterization of the samples through the M(H) plots showed a very low coercivity value for both samples, being 53 Oe for FeO-1 and 10 Oe for FeO-2, indicating the very weak ferromagnetic character of the synthesized iron oxide species. Even though both organic acids under solvothermal conditions permit to obtain coated IONPs in one pot reaction, l-serine produces a more narrow-size distribution.